Kajian Harga Air Daerah Irigasi Muara Uwai Kecamatan Bangkinang Seberang Kabupaten Kampar - Hendra Mulyadi Muslim; Bambang Sujatmoko; Mudjiatko Mudjiatko (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Irrigation area of Muara Uwai with 824 ha of service area is now decreasing deterioration due to the damages that happen on the irrigation network around the irrigation area. Those problem caused the field that supposed to be the farm field to change allocation into fishponds and plantations. Thus a solution must be deviced to allow the irrigation network to get back to it optimum by applying the price of irrigation water. The price of irrigation water in a retribution imposed on farmer to fulfil the renovation cost, maintenance and operartional cost of the irrigation area. The estimation of the initial renovation cost of the irrigation area is Rp 44.757.094,03, the maintenance and operational cost of the irrigatian area every years is Rp 91.103.108,98 and the expense for watergate change on the 10th year is Rp. 130.145.007,00. The interest rate used is the minimum rate of bank commercial rate at 10%. The investment period choosen on this research is 14 years that gives the payback period of the rate that stand below the investment years and annual benefit wih positive value which means the solution is feasible. The value on the price of irrigation water with investment period of 14 years is 10,516.65 per hectare per month.Keywords : cost estimation, irrigation water price, irrigation network, maintenance and operational, investment period.